Overview of Food Safety and Labeling Regulatory Frameworks in Morocco - Boulaajine, Samya; Hajjaj, Hassan (The North African Journal of Food and Nutrition Research, 2025)
Background: Food fraud and mislabeling pose substantial risks to consumer health, economic integrity, and public trust in the food supply chain. In Morocco, the increasing consumption of processed foods and the prevalence of informal markets further exacerbate the threats associated with food labeling violations.Aims: This review aims to assess the current state of food labeling and safety regulation in Morocco. A central focus is to analyze the role and effectiveness of the National Office for Food Safety (ONSSA) in monitoring and enforcing these labeling standards.Methods: A documentary research approach was employed, involving a comprehensive review of scientific literature, including peer-reviewed articles, as well as official reports and regulatory texts with a particular emphasis on Moroccan legal frameworks.Results: Morocco has achieved notable progress in regulating food labeling, particularly through the implementation of Decree No. 2–12–389 and the inspection efforts of the ONSSA. However, significant enforcement challenges persist, especially in informal markets and in addressing ambiguous health claims. Annually, a considerable volume of food is seized due to labeling violations. Further progress is hindered by the lack of widespread front-of-pack labeling and inconsistencies in relation to existing regulations.Conclusions: While Morocco has successfully strengthened its food labeling infrastructure, further improvements are necessary. Enhancing regulatory clarity, expanding producer education, and promoting consumer awareness—particularly through tools such as front-of-pack labeling—are essential for advancing food safety and public health. Greater alignment with international standards and the adoption of digital traceability systems will further support the modernization of Morocco's food system.Keywords: Food products; Labeling; Claims; Fraud; Control; Safety.
Keywords: Food products; Labeling; Claims; Fraud; Control; Safety